Perceptions of disability among parents of children with disabilities in Nicaragua: Implications for future opportunities and health care access - Matt, Susan B (Disability Studies Quarterly, 2014)
The purposes of this study were to explore caregiver perceptions of the origin of their children's disabilities, aspirations for their children's future, and the frequency with which they sought health care and rehabilitation services for their children with disabilities. A qualitative descriptive design using face-to-face semi-structured interviews of 13 caregivers of children with disabilities was employed. Caregivers cited biomedical explanations, as well as beliefs in superstitious, traditional, and religious-based causes of disability. Respondents reported limited access to medical care and rehabilitation services. Nevertheless, caregivers have hope for their children's futures. Increased global medical volunteer involvement has the potential to improve access to care and rehabilitation services.